Peulerneca ubaira gen. et sp. nov.: A new Lernecina cricket with white and hyaline forewings from the Brazilian Atlantic Forest (Phalangopsidae, Luzarinae, Lernecina) - de Assis Ganeo De Mello, Francisco [UNESP]; Souza, Matheus D'oran [UNESP]; Tavares, Gustavo Costa (Magnolia Press, 2023)
Here we describe a new genus and species of cricket belonging to Lernecina from the Brazilian Atlantic Forest. It is presently known only from Ubaíra, State of Bahia, Brazil. The new genus is the only known member of this subtribe having males with a mostly white and hyaline dorsal field of the forewing (an additional genus with that condition is in the process of being described).
Keywords: Brazil; coastal Atlantic Forest; cricket; description; South America; taxonomy